The Character of Nighttime Architecture on Letjen Soeprapto Street at Semarang Old Town - Ariadi Susanto (Departement of Architecture, Universitas Islam Indonesia, 2019)
Since the old town of Semarang preened to be proposed to UNESCO as a heritage city, many tourists have been visiting the area during the day and night, especially the Letjen Suprapto street, which is the main corridor of the old town of Semarang. Business people also help enliven the activity by reviving old buildings that were not functioning. Facade is an important element in architecture and becomes a major concern in strengthening the character of colonial architecture in the old town of Semarang. Architecture that is characterized by door openings and windows with a height and width with thick walls, gives the impression of space that is more pronounced in the composition of architectural elements in the facade of the building. At night, the role of artificial lighting attached to the outer walls of the building, lighting from inside the building, and lighting the environment will lead to different perceptions of the facade of the building. Parts of the dark facade elements can be a bright part and vice versa, as part of the visual relationship between the front and inside of the building which shows the existence of a figure-ground relation in the scope of the facade of the building. In order to examine the character of nighttime architecture in this corridor, reviews are done on several buildings that have the composition of facade elements and use artificial lighting as a building factor for nighttime architecture.Keywords: nighttime architecture, artificial lighting, building facade